2017
DOI: 10.1177/2055217317747624
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation correlates with disease duration in multiple sclerosis (MS): Novel insights into the MS-associated prothrombotic state

Abstract: BackgroundThrombin is well recognised for its role in the coagulation cascade but it also plays a role in inflammation, with enhanced thrombin generation observed in several inflammatory disorders. Although patients with multiple sclerosis (MS) have a higher incidence of thrombotic disease, thrombin generation has not been studied to date.ObjectivesThe aim of this study was to characterise calibrated automated thrombography parameters in patients with relapsing–remitting MS (RRMS) and primary progressive MS (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Overall, the lower FXII:ratio and longer TG time parameters suggested that in part of MS patients (i) FXII could be less active per antigen unit and (ii) FXII response to contact activation and its support to the intrinsic coagulation pathway could be reduced. Interestingly, it has been recently reported that in TG, triggered by extrinsic activation, time parameters were shorter in MS patients ( 23 ), which does not conflict with our data because extrinsic TG does not explore FXII contribution. Noteworthy, both the intrinsic TG, first reported in our study, and the extrinsic TG ( 23 ) tightly depend on activation and activity of coagulation factors in the common pathway, essential to generate thrombin.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Overall, the lower FXII:ratio and longer TG time parameters suggested that in part of MS patients (i) FXII could be less active per antigen unit and (ii) FXII response to contact activation and its support to the intrinsic coagulation pathway could be reduced. Interestingly, it has been recently reported that in TG, triggered by extrinsic activation, time parameters were shorter in MS patients ( 23 ), which does not conflict with our data because extrinsic TG does not explore FXII contribution. Noteworthy, both the intrinsic TG, first reported in our study, and the extrinsic TG ( 23 ) tightly depend on activation and activity of coagulation factors in the common pathway, essential to generate thrombin.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, it has been recently reported that in TG, triggered by extrinsic activation, time parameters were shorter in MS patients ( 23 ), which does not conflict with our data because extrinsic TG does not explore FXII contribution. Noteworthy, both the intrinsic TG, first reported in our study, and the extrinsic TG ( 23 ) tightly depend on activation and activity of coagulation factors in the common pathway, essential to generate thrombin. Although indirectly, our study does not support the presence of a prothrombotic state in the MS patients under study.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, relapse free time negatively correlated with level of either prothrombin, factor XII, or factor X indicating disease exacerbation as a condition characterized by increased coagulation activity (9). Similarly, the speed of thrombin generation was found faster in relapsing-remitting than in primary progressive MS or healthy controls and correlated with time from clinical diagnosis likely reflecting the differential active proinflammatory state in each MS subtype (72). Dermatan sulfate and heparin inhibit the generation of thrombin activity and both have been demonstrated to be effective therapeutic agent for EAE (7375).…”
Section: Thrombinmentioning
confidence: 99%
“…Of note, relapse-free time negatively correlated with levels of prothrombin, factor XII, or factor X, indicating that disease exacerbation is characterized by increased coagulation activity (31). Interestingly, the speed of thrombin generation was higher in relapsing-remitting than in primary progressive MS or healthy controls and correlated with time from clinical diagnosis, likely suggesting a differential active proinflammatory state in each MS subtype (32). By the proteomics approach, some serum proteins such as antithrombin, ceruloplasmin, clusterin, apolipoprotein E, and complement C3 were differently expressed in RRMS patients compared to controls (33).…”
Section: Introductionmentioning
confidence: 98%